Behaviour of hop-derived branched-chain fatty acids during fermentation and their sensory effect on hopped beer flavours - Takoi, Kiyoshi (BrewingScience, 2019)
In this study, branched-chain fatty acids (isobutyric acid, isovaleric acid, and 2-methylbutyric acid) were focused on. These fatty acids were originated from malts, hops, and yeast fermentation. It was thought that the concentrations of isobutyric acid and isovaleric acid in both wort and beer were affected by hops used for brewing, and that the behaviour of 2-methylbutyric acid might be less affected without/with hops. When fresh hops were used, these fatty acids were at relatively narrow ranges in both worts and beers. From the analysis by scatter diagrams of the concentrations of three fatty acids and corresponding ethyl esters (ethyl isobutyrate, ethyl isovalerate, and ethyl 2-methylbutyrate), it was suggested that the concentration of ethyl isovalerate showed relatively good correlation with isovaleric acids derived from hops, that ethyl 2-methylbutyrate in beer could be mainly affected by 2-methylbutyric acid generated during fermentation, and that ethyl isobutyrate in beer could be affected by hop-derived isobutyric esters rather than by hop-derived isobutyric acid. In the viewpoint of sensory effect, it was suggested that branched-chain fatty acids could enhance the flavours of monoterpene alcohols, and that only threshold levels of fatty acids were enough for this effect. In addition, it was assumed that branched-chain fatty acids could change total flavour profile of the mixture of monoterpene alcohols at threshold levels.